Gender differences in advanced activities of daily living: evidence from the longitudinal study of health and aging in Mexico 2012–2018 - Sánchez-Rodríguez, Martha A.; Zacarías-Flores, Mariano; Castañeda-Sánchez, Lesly Estefanía; Mendoza-Núñez, Víctor Manuel (Frontiers in Aging, 2025)
BackgroundPerforming advanced activities of daily living (AADLs) is a component of healthy aging (HA) because it involves functional capacity. The ability to perform them can be hampered by several factors, which appear different for men and women.ObjectiveTo evaluate the performance data of AADLs in older Mexican adults from Mexican Health and Aging Study (MHAS) from 2012 to 2018 and to determine the risk factors for not performing AADLs.MethodsA secondary longitudinal analysis of the 2012 and 2018 waves of the MHAS was conducted. Adults ≥60 years, from both sexes, who answered at least eight of the nine questions analyzed, without or only mild cognition impairment in 2012, and who were interviewed in both waves were included. An AADL construct with nine questions from the MHAS including physical/leisure, social and productive domains was used. The Cox proportional regression model was used as a longitudinal analysis to determine the risk factors to not perform ≥3 AADLs.Results4,738 adults were ≥60 years old and met the inclusion criteria, 2,617 were women (54%). Total AADLs were diminished in 2018 (2.68 ± 1.39 vs. 2.61 ± 1.34, p < 0.01); however, women performed more AADLs in 2018 than in 2012, contrary to men. Risk factor to not perform ≥3 AADLs in women were age ≥70 years and sedentary lifestyle. Men have the same risk factors in addition to low scholarship and live in urban locations. After control by confounder factors, the risk of not performing ≥3 AADLs was in the overall model HR = 1.25 (95% confidence intervals (CI): 1.17–1.37), women HR = 1.20 (95%CI: 1.08–1.32), and men HR = 1.26 (95%CI: 1.17–1.35).ConclusionOur findings show that the execution of ≥3 AADLs is age-dependent over 80 years. Although this capacity could be gender-dependent, the environment and public policies can be determining factors.